SATISFACTION FACTORS FROM THE WORK OF MEDICAL PROFESSIONALS, WORKING IN EMERGENCY MEDICAL CARE IN THE REPUBLIC OF BULGARIA - D. Todorova (Trakia Journal of Sciences)
To study more comprehensively, analyze and summarize the satisfaction factors of the professional activity of the medical teams from CEMC. Preliminary interviews were conducted with medical professionals working at CEMC. On this basis, a questionnaire was developed, surveying through a sociological method the opinion of medical professionals from the Centers for Emergency Medical Care. Medical professionals, providing emergency medical care, face a number of challenges, which in turn have a direct impact on job satisfaction. We studied the satisfaction factors influencing the professional activity of the medical professionals working in the emergency medical care centers and their manifestations. The degree of professional satisfaction and its manifestations can be conditionally classified into 4 levels - high, medium, low satisfaction and complete dissatisfaction. The satisfaction factors and the level of overall satisfaction of the medical professionals working in the emergency medical care in the Republic of Bulgaria represent a number of complicated regularities, derived on a scientific basis. For the satisfaction of the emergency medical care professionals, it is necessary to provide factors that prevent dissatisfaction with the work and the organization of work, while, at the same time ensure conditions for the normal course of the activity, professional achievements and development.